International Practices to Promote Budget Literacy : Key Findings and Lessons Learned - Masud, Harika; Pfeil, Helene; Agarwal, Sanjay; Gonzalez Briseno, Alfredo (Washington, DC: World Bank, 2017)
Budget literacy is defined as 'the ability to read, decipher, and understand public budgets to enable and enhance meaningful citizen participation in the budget process'. It is comprised of two main parts - (i) a technical understanding of public budgets, including familiarity with government spending, tax rates and public debt and; (ii) the ability to engage in the budget process, comprising of practical knowledge on day-to-day issues, as well as an elementary understanding of the economic, social and political implications of budget policies, the stakeholders involved and when and how to provide inputs during the annual budget cycle.